Immunosuppression Has Long-Lasting Effects on Circulating Follicular Regulatory T Cells in Kidney Transplant Recipients - Niu, Qian; Mendoza Rojas, Aleixandra; Dieterich, Marjolein; Roelen, Dave L.; Clahsen-van Groningen, Marian C.; Wang, Lanlan; van Gelder, Teun; Hesselink, Dennis A.; van Besouw, Nicole M.; Baan, Carla C. (Frontiers in Immunology, 2020)
Background: FoxP3+ follicular regulatory T cells (Tfr) have been identified as the cell population controlling T follicular helper (Tfh) cells and B cells which, are both involved in effector immune responses against transplanted tissue. Methods: To understand the biology of Tfr cells in kidney transplant patients treated with tacrolimus and mycophenolate mofetil (MMF) combination immunosuppression, we measured circulating (c)Tfh and cTfr cells in peripheral blood by flow cytometry in n=211 kidney transplant recipients. At the time of measurement patients were 5-7 years after transplantation. Of this cohort of patients, 23.2% (49/211) had been previously treated for rejection. Median time after anti-rejection therapy was 4.9 years (range 0.4–7 years). Age and gender matched heathy individuals served as controls. Results: While the absolute numbers of cTfh cells were comparable between kidney transplant recipients and healthy controls, the numbers of cTfr cells were 46% lower in immunosuppressed recipients (p<0.001). More importantly, in transplanted patients, the ratio of cTfr to cTfh was decreased (median; 0.10 vs 0.06), indicating a disruption of the balance between cTfr and cTfh cells. This shifted balance was observed for both non-rejectors and rejectors. Previous pulse methylprednisolone or combined pulse methylprednisolone + intravenous immunoglobulin anti-rejection therapy led to a non-significant 30.6% (median) and 51.2% (median) drop in cTfr cells, respectively when compared to cTfr cell numbers in transplant patients who did not receive anti-rejection therapy. A history of alemtuzumab therapy did lead to a significant decrease in cTfr cells of 85.8% (median) compared with patients not treated with anti-rejection therapy (p<0.0001). No association with tacrolimus or MMF pre-dose concentrations was found. Conclusion: This cross-sectional study reveals that anti-rejection therapy with alemtuzumab significantly lowers the number of cTfr cells in kidney transplant recipients. The observed profound effects by these agents might dysregulate cTfr functions.